Відповідь:
Покрокове пояснення:
(х - (9 * 3/7)) + (5 * 1/3) = 6 5/14
(х - (27/7)) + (35/21) = 6 5/14
21 * (х - 27/7) + 21 * (35/21) = 21 * (6 5/14
21x - 9 * 3 + 35 = 90 10/14
90 + 10/14 = 90 + 5/7 = 630/7 + 5/7 = 635/7
21x - 27 + 35 = 635/7
21x + 8 = 635/7
21x = 579/7
x = 579/147
x = 3 * (193/49)
x = 12
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
Покрокове пояснення:
(х - (9 * 3/7)) + (5 * 1/3) = 6 5/14
(х - (27/7)) + (35/21) = 6 5/14
21 * (х - 27/7) + 21 * (35/21) = 21 * (6 5/14
21x - 9 * 3 + 35 = 90 10/14
90 + 10/14 = 90 + 5/7 = 630/7 + 5/7 = 635/7
21x - 27 + 35 = 635/7
21x + 8 = 635/7
21x = 579/7
x = 579/147
x = 3 * (193/49)
x = 12